A 3p interstitial deletion in two monozygotic twin brothers and an 18‐year‐old man: Further characterization and review. Issue 10 (15th August 2013) - Maria Christina Schwaibold, Eva; Zoll, Barbara; Burfeind, Peter; Hobbiebrunken, Elke; Wilken, Bernd; Funke, Rudolf; Shoukier, Moneef
Abstract An increasing number of patients with 3p proximal deletions were reported in the previous decade, but the region responsible for the main features such as intellectual disability (ID) and developmental delay is not yet characterized. Here we report on two monozygotic twin brothers of 2 10/12 years and an 18‐year‐old man, all three of them displaying severe ID, psychomotoric delay, autistic features, and only mild facial dysmorphisms. Array CGH (aCGH), revealed a 6.55 Mb de novo interstitial deletion of 3p14.1p14.3 in the twin brothers and a 4.76 Mb interstitial deletion of 3p14.1p14.2 in the 18‐year‐old patient, respectively. We compared the malformation spectrum with previous molecularly well‐defined patients in the literature and in the DECIPHER database (Database of Chromosomal Imbalance and Phenotype in Humans using Ensembl Resources; http://decipher.sanger.ac.uk/). In conclusion, the deletion of a region containing 3p14.2 seems to be associated with a relative concise phenotype including ID and developmental delay. Thus, we hypothesize that 3p14.2 is the potential core region in 3p proximal deletions. The knowledge of this potential core region could be helpful in the genetic counselling of patients with 3p proximal deletions, especially concerning their phenotype. © 2013 Wiley Periodicals, Inc.